The Criminal Sanctions Implementation of Personnel Sexual Violence on Under Age’s Children (Minors) - Afandi Afandi; Umar Ma'ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
The objectives of this research are: To analyze and explain implementation of criminal sanctions for perpetrators of sexual violence against minors. To analyze and explain constraints and solutions implementation of criminal sanctions for perpetrators of sexual violence against minors. The method used by researchers is a sociological juridical legal approach and the specifications in this study are descriptive. Based on the results of the research that the implementation of criminal sanctions for perpetrators of sexual violence against minors according to Act No. 23 of 2002 can be implemented and applies Article 82 of Act No. 23 of 2002 and Article 290 paragraph 2 of the Criminal Code that the defendant is proven to have fulfilled the objective elements and The subjective elements contained in both articles carry a maximum penalty of 15 years in prison and a minimum of 3 years in prison. The obstacles are: a) when the perpetrator of a criminal act of sexual violence against children knows that he has been reported by the victim to the police. b) The investigator has limited time in processing files of the crime. c) Lack of information about the perpetrator also makes it more difficult for investigators to find the perpetrator. d) It is difficult for the investigator to obtain information from the victim who has severe trauma. e) In investigating criminal acts of sexual violence against children, one of the steps the investigator takes to obtain evidence of a criminal act of sexual violence against children is to take a post mortem. The solution is: a) the investigator takes steps to collaborate with the police from various regions to find the whereabouts and secure the perpetrator.